Flux Analysis of the Metabolism of Clostridium cellulolyticum Grown in Cellulose-Fed Continuous Culture on a Chemically Defined Medium under Ammonium-Limited Conditions - Desvaux, Mickaël (American Society for Microbiology, 2001)
An investigation of cellulose degradation by the nonruminal, cellulolytic, mesophilic bacterium Clostridium cellulolyticum was performed in cellulose-fed chemostat cultures with ammonium as the growth-limiting nutrient. At any dilution rate (D), acetate was always the main product of the catabolism, with a yield of product from substrate ranging between 37.7 and 51.5 g per mol of hexose equivalent fermented and an acetate/ethanol ratio always higher than 1. As D rose, the acetyl coenzyme A was rerouted in favor of ethanol pathways, and ethanol production could represent up to 17.7% of the carbon consumed. Lactate was significantly produced, but with increasing D, the specific lactate production rate declined, as did the specific rate of production of extracellular pyruvate. The proportion of the original carbon directed towards phosphoglucomutase remained constant, and the carbon surplus was balanced mainly by exopolysaccharide and glycogen biosyntheses at high D values, while cellodextrin excretion occurred mainly at lower ones. With increasing D, the specific rate of carbon flowing down catabolites increased as well, but when expressed as a percentage of carbon it declined, while the percentage of carbon directed through biosynthesis pathways was enhanced. The maximum growth and energetic yields were lower than those obtained in cellulose-limited chemostats and were related to an uncoupling between catabolism and anabolism leading to an excess of energy. Compared to growth on cellobiose in ammonium-limited chemostats (E. Guedon, M. Desvaux, and H. Petitdemange, J. Bacteriol. 182:2010–2017, 2000), (i) a specific consumption rate of carbon of as high as 26.72 mmol of hexose equivalent g of cells(−1) h(−1) could not be reached and (ii) the proportions of carbon directed towards cellodextrin, glycogen, and exopolysaccharide pathways were not as high as first determined on cellobiose. While the use of cellobiose allows highlighting of metabolic limitation and regulation of C. cellulolyticum under ammonium-limited conditions, some of these events should then rather be interpreted as distortions of the metabolism. Growth of cellulolytic bacteria on easily available carbon and nitrogen sources represents conditions far different from those of the natural lignocellulosic compounds.